2020
DOI: 10.3390/ijms21093140
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CEMIP in Chondrocytes by Inflammatory Cytokines: Underlying Mechanisms and Potential Involvement in Osteoarthritis

Abstract: In patients with osteoarthritis (OA), there is a decrease in both the concentration and molecular size of hyaluronan (HA) in the synovial fluid and cartilage. Cell migration-inducing hyaluronidase 1 (CEMIP), also known as hyaluronan (HA)-binding protein involved in HA depolymerization (HYBID), was recently reported as an HA depolymerization-related molecule expressed in the cartilage of patients with OA. However, the underlying mechanism of CEMIP regulation is not well understood. We found that CEMIP expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…IL-1β can upregulate MMP3 and MMP9 and ADAMTs by activating IL-17, thereby promoting joint inflammation and inducing chondrocyte apoptosis [14]. Ohtsuki et al [15] observed that IL-1β is also involved in upregulating Cell migration-inducing hyaluronidase 1 (CEMIP), which induces the degradation of hyaluronan in ECM. Several miRNAs (miR-34a, miR-30a, miR-145, and miR-27a) are activated by IL-1β and participate in progression of OA by activating matrix-degrading enzymes and downstream inflammatory pathways such as MAPK and NF-κB [16].…”
Section: Resultsmentioning
confidence: 99%
“…IL-1β can upregulate MMP3 and MMP9 and ADAMTs by activating IL-17, thereby promoting joint inflammation and inducing chondrocyte apoptosis [14]. Ohtsuki et al [15] observed that IL-1β is also involved in upregulating Cell migration-inducing hyaluronidase 1 (CEMIP), which induces the degradation of hyaluronan in ECM. Several miRNAs (miR-34a, miR-30a, miR-145, and miR-27a) are activated by IL-1β and participate in progression of OA by activating matrix-degrading enzymes and downstream inflammatory pathways such as MAPK and NF-κB [16].…”
Section: Resultsmentioning
confidence: 99%
“…We also confirmed that this compound significantly suppressed the activation of MAPK signaling pathway molecules such as Erk1/2, p38, and JNK in IL-1β-induced OUMS27 cells in a concentration-dependent manner. MAPK signaling is one of the key signaling pathways that mediate inflammation responses and cartilage degradation and promote the pathological progression of OA [ 9 , 15 , 16 ]. These results indicate that 3-B2 could attenuate MMP and ADAMTS expression as well as chondrocyte inflammation by suppressing MAPK signaling pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates were centrifuged at 20,000× g for 15 min, and total protein concentrations were quantified using a Bio-Rad DC TM Protein Assay Kit (Bio-Rad Laboratories, Hercules, CA, USA), with bovine serum albumin used as the standard protein. Cell lysates were mixed with 4× reducing sample buffer, denatured at 95 °C for 5 min, separated on 10% SDS-PAGE gels, and transferred onto polyvinylidene difluoride (PVDF) membranes (Merck Millipore Ltd., Darmstadt, Germany) as previously described [ 15 , 39 ]. The primary antibodies were anti-MMP13 (1:400), anti-ERK (1:1000), anti-phospho-ERK (1:1000), anti-p38 (1:1000), anti-phospho-p38 (1:1000), anti-JNK (1:1000), anti-phospho-JNK (1:1000), and anti-β-actin (1:10,000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also indicated that HYAL1 and HYAL2 expression was up-regulated in OA chondrocytes; however, suppression of HYBID with siRNA eliminated HA depolymerization activity, and siRNA against HYAL1 and HYAL2 did not suppress HA depolymerization. Ohtsuki et al 16 reported that CEMIP/ HYBID expression was transiently increased by IL-1b stimulation in chondrocytic cells in vitro. These results suggest that HYBID is highly expressed in OA cartilage and synovial tissues and might play a central role in HA depolymerization under inflammatory conditions.…”
Section: Hyaluronidase In Developed Oa Potential Therapeutic Interventionmentioning
confidence: 99%